Use of nanoparticle concentration as a tool to understand the structural properties of colloids - Ribeiro, Lígia Nunes De Morais; Couto, Verônica Muniz; Fraceto, Leonardo Fernandes [UNESP]; De Paula, Eneida (Springer Nature, 2018)
Elucidation of the structural properties of colloids is paramount for a successful formulation. However, the intrinsic dynamism of colloidal systems makes their characterization a difficult task and, in particular, there is a lack of physicochemical techniques that can be correlated to their biological performance. Nanoparticle tracking analysis (NTA) allows measurements of size distribution and nanoparticle concentration in real time. Its analysis over time also enables the early detection of physical instability in the systems not assessed by subtle changes in size distribution. Nanoparticle concentration is a parameter with the potential to bridge the gap between in vitro characterization and biological performance of colloids, and therefore should be monitored in stability studies of formulations. To demonstrate this, we have followed two systems: extruded liposomes exposed to increasing CHCl3 concentrations, and solid lipid nanoparticles prepared with decreasing amounts of poloxamer 188. NTA and dynamic light scattering (DLS) were used to monitor changes in nanoparticle number and size, and to estimate the number of lipid components per particle. The results revealed a strong negative correlation between particle size (determined by DLS) and concentration (assessed by NTA) in diluted samples, which should be adopted to monitor nanocolloidal stability, especially in drug delivery.